2001
DOI: 10.1007/s00204-001-0282-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of UDP-glucuronosyltransferases in rat liver microsomes by natural mutagens and carcinogens

Abstract: Eight toxic compounds of natural origin present in the human diet or used as drugs were tested as inhibitors of UDP-glucuronosyltransferase (UGT) activity in rat liver microsomes with 1-naphthol (1-NA), phenolphthalein (PPh) and 4-nitrophenol (4-NP) as substrates. Strong inhibitory effects were observed with tannic acid (tannin) and the antifungal drug griseofulvin (GF): at a concentration of 1 mM, the two compounds completely suppressed the glucuronidation of 1-NA and PPh, respectively. A concentration of 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Early studies reported the effects of drugs and dietary compounds on UGT activity in isolated microsomes or in rats without detailing the specific UGT isozymes involved (9, 10). Liver microsomal glucuronidation of estradiol and estrone was inhibited by green and black teas, along with a constituent catechin [(-)-epigallocatechin gallate] and several flavonoids (kaempferol, quercetin, rutin, flavone, naringenin, hesperetin) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies reported the effects of drugs and dietary compounds on UGT activity in isolated microsomes or in rats without detailing the specific UGT isozymes involved (9, 10). Liver microsomal glucuronidation of estradiol and estrone was inhibited by green and black teas, along with a constituent catechin [(-)-epigallocatechin gallate] and several flavonoids (kaempferol, quercetin, rutin, flavone, naringenin, hesperetin) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the SERS enhancement, this system can also be used to modulate the fluorescence intensity of adsorbed chromophores as a function of temperature. [13] The synthesis of the core-shell Au@pNIPAM colloids has been described in detail elsewhere [7] and involves initial growth of a thin polystyrene (PS) shell on cetyl trimethyl ammonium bromide (CTAB) coated, 67 nm gold nanoparticles, followed by polymerization of N-isopropylacrylamide (NIPAM) and a cross-linker (N,N-methylenebisacrylamide; see Experimental Section for details). Through a rational choice of model analytes, we demonstrate the application of these thermoresponsive hybrid materials for surface-enhanced Raman scattering, fluorescence, and resonance Raman scattering (SERS, SEF, and SERRS, respectively).…”
mentioning
confidence: 99%
“…The endogenous bile acids (cholic acid, chenodeoxycholic acid, and deoxycholic acid) have been reported to inhibit bilirubin glucuronidation in digitonin-disrupted rat liver microsomes. 24 Impairment of the glucuronidation reaction by clinically used drugs is an important aspect of UGT inhibition studies. It was reported that some drugs are able to interfere with the glucuronidation of endogenous component, therapeutic agents, and xenobiotics.…”
Section: Discussionmentioning
confidence: 99%